Dispersive optical solitons and modulation instability analysis of Schrodinger-Hirota equation with spatio-temporal dispersion and Kerr law nonlinearity - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Academic Press Ltd- Elsevier Science Ltd, 2018)
This paper obtains the dark, bright, dark-bright or combined optical and singular solitons to the perturbed nonlinear Schrodinger-Hirota equation (SHE) with spatio-temporal dispersion (STD) and Kerr law nonlinearity in optical fibers. The integration algorithm is the Sine-Gordon equation method (SGEM). Furthermore, the modulation instability analysis (MI) of the equation is studied based on the standard linear-stability analysis and the MI gain spectrum is got. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sine-Gordon equation method; Schrodinger-Hirota equation; Optical solitons; Modulation instability analysis